FREQUENCY AND FACTORS ASSOCIATED WITH COGNITIVE AND ANXIETY-DEPRESSIVE DISORDERS IN PATIENTS WITH MOTOR NEURON DISEASE (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the frequency and associated factors of cognitive and anxiety-depressive disorders in patients with motor neuron disease. METHODOLOGY: A cross-sectional study was conducted at SMBBMU, Larkana, on a sample of 246 patients aged 18 to 70 years, either gender, diagnosed with motor neuron disease with a duration of at least 6 months. Cognitive impairment, anxiety, and depression were assessed using MMSE, SAS, and SDS scales. Demographic and clinical factors, including age, gender, education, comorbidities, and smoking status, were analyzed for associations. Data was processed using SPSS version 26. RESULTS: The mean age of the participants was found to be 55.88 ± 13.34 years. Among the 246 patients, 61.4% were male, and 38.6% were female. Cognitive impairment was found in 16.3% (MMSE: 27.18 ± 5.28), depression in 20.3% (SDS: 43.76 ± 14.27), and anxiety in 82.9% (SAS: 64.02 ± 21.74). Significant associations were observed for education (p=0.045), COPD (p=0.041), and age (p=0.005). CONCLUSION: Cognitive and anxiety-depressive disorders are common in patients affected by motor neuron disease (MND). Educational status and COPD were identified with cognitive impairment and depression with older age. Implementing early screening as well as comprehensive management strategies is critical to improving outcomes and quality of life for patients. Further studies are needed to better understand the underlying mechanisms and identify effective intervention targets.